Polymer Derived Ceramics with Negative Thermal Expansion Fillers: Zirconium Tungstate. Issue 6 (28th March 2019) - Fedorova, Anna; Scheffler, Michael
Abstract : Novel‐type bulk polymer derived ceramics are manufactured with negative thermal expanding zirconium tungstate (ZrW2 O8 ) as filler material. A pressure‐induced phase transformation of the α ‐ZrW2 O8 phase into the γ ‐ZrW2 O8 is observed, caused by high thermal mismatch stresses between the polymer derived ceramic matrix and the filler particles. The zirconium tungstate phase influences the overall thermal expansion behavior, and an additional annealing step is added to the manufacturing process to trigger the re‐transformation of the filler and to restore the negative thermal expansion behavior of the bulk polymer derived ceramic. Abstract : Zirconium tungstate fillers with a negative thermal expansion embedded in a polymer derived ceramic matrix, a pressure‐induced phase change from α ‐ZrW2 O8 to γ ‐ZrW2 O8 during pyrolysis at 700 °C is reversed by annealing the materials at 200 °C and subsequent cooling. This results in a γ  → β transformation at 200 °C and a β → α transformation when cooled to room temperature. The composite's thermal expansion coefficient is negative.